<span>(-3,5) (-5,6)
slope = 5-6 / -3 --5
</span><span>slope = -1 / 2
</span>
If you would like to solve the equation 3 * (3 * x - 1) + 2 * (3 - x) = 0, you can calculate this using the following steps:
3 * (3 * x - 1) + 2 * (3 - x) = 0
3 * 3 * x - 3 * 1 + 2 * 3 - 2 * x = 0
9 * x - 3 + 6 - 2 * x = 0
7 * x + 3 = 0
7 * x = - 3 /7
x = - 3/7
The correct result would be - 3/7.
IF MARTHA EARNS 3.25/HOUR FRO BABYSITTING (SHE IS UNDERPAID!)
IN 1.5 HOURS=3.25*1.5=4.88 DOLLARS
IN 2.5 HOURS=3.25*2.5=8.13 DOLLARS
IN 3.5 HOURS=3.25*3.5=11.38 DOLLARS
Answer:
Step-by-step explanation:
x < 12